AB0724 IS THERE A LINK BETWEEN RADIOGRAPHIC SACROILIITIS AND HIP INVOLVEMENT IN SPONDYLOARTHRITIS?. (13th June 2020) - Rahmouni, S.; Slouma, M.; Dhahri, R.; Gharsallah, I.; Boussetta, N.; Gueddich, H.; Ajili, F.; Metoui, L.; Louzir, B.
Abstract : Background: Hip involvement is a common feature in spondyloarthritis (SpA). Whether the hip is part of the axial or appendicular skeletal is still a matter of discussion. Objectives: We aimed to assess the relationship between sacroiliitis, spinal and hip involvement in SpA. Methods: Patients with SpA diagnosed according to the assessment of Spondyloarthritis International Society criteria were included in this retrospective cross-sectional study. The modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) and the Bath Ankylosing Spondylitis Radiology Index-spine (BASRI-s) were used to assess the radiographic involvement of the spine. The sacroiliac joints were scored according to the modified New York criteria. Radiological hip involvement was scored using the Bath Ankylosing Spondylitis Radiology Index hip (BASRI-h). Patients were divided into two groups: G0 including patients without hip involvement and G1 patients with hip involvement. Results: We included 112 patients with a sex ratio of 2.4. The average SpA symptom duration was 9.33 ± 8.93 years. The diagnostic delay was 42.92 ± 52 months. Radiographic hip involvement was noted in 39.28% of cases. It was bilateral in 31 patients (70.4%). The total number of coxitis was 75. Severe and moderate hip involvement (BASRI-h ≥ 3) affected 21 hips. The most common radiographic pattern was early coxitis (n=31, 41.3%) followed by the destructive form (n=22, 29.3%, mimicking-osteoarthritis form (n=15, 20%), condensing form (n=5, 6.6%) and ankylosing form (n=2, 2%). Radiographic sacroiliitis was noted in 75.8% of patients. It was bilateral in 91.7% of cases. Among the 161 sacroiliac joints fulfilling the m-New-york criteria, 32.9% had grade 4 and 37.2% had grade 3. The mean mSASSS was 10.26 ± 15. The mean BASRI-t, BASRI-C, and BASRI-L were 3.99 ± 2.9, 0.89 ± 1.3, and 1.1 ± 1.3 respectively. Radiographic sacroiliitis was more common in patients with hip involvement (G1) (90.9% vs 68.2%, p=0.00). Patients in G1 had higher mSASSS (15.78 ± 18.24 vs 6.29 ± 11.85, p=0.01), BASRI-L (1.73±1.46 vs 0.75 ± 1.131, p=0.009), and BASRI-s (5.46 ± 3.02 vs 3.19 ± 2.46, p< 10 -3 ) than patients in G2. There was no significant difference between the two groups regarding the BASRI-C. Multivariable analysis revealed that radiographic sacroiliitis was associated with hip involvement (OR=14.81, 95%, [1.1-198], p=0.042). When comparing patients with severe and moderate hip involvement (BASRI-h ≥ 3) and those with mild involvement, we didn't find significant differences regarding BASRIs, BASR-L, BASRI-c, mSASSS, and sacroiliac involvement. Conclusion: As reported in previous studies [1], we concluded that structural axial lesions were higher in patients with coxitis. Structural damage to the sacroiliac joint in SpA was predictive of hip involvement. We suggest that sacroiliitis, spinal and hip involvement are part of the same spectrum. References: [1]Chen H-A, Chen C-H, Liao H-T, Lin Y-J, Chen P-C, Chen W-S, et al. Factors associated with radiographic spinal involvement and hip involvement in ankylosing spondylitis. Semin Arthritis Rheum. 2011;40 (6):552-8 Disclosure of Interests: None declared